Mouse Models of Autoimmune Diabetes: The Nonobese Diabetic (NOD) Mouse - Chen, Dawei (Methods Mol Biol, 2020)
There are now a number of different mouse models for type 1 diabetes. The best known is the nonobese diabetic (NOD) mouse which has a genetic susceptibility to autoimmune diabetes with some features that are similar to human type 1 diabetes. The mice also have a propensity to other autoimmune diatheses, including autoimmune thyroid disease and sialadenitis. In addition, it is well known that environmental factors affect the incidence of disease in these mice. While there are other rodent models, including numerous transgenic and knockout models, as well as those that express human proteins, none of these develop spontaneous diabetes over a period of time, when the natural history can be studied. We focus here on the unmanipulated NOD mouse and discuss features of the husbandry and investigation of the mice that allow for use of these long-studied mice in the pathogenesis of an autoimmune type of diabetes.